PSYCHOPHYSIOLOGICAL FOUNDATIONS OF ANXIETY IN PREGNANT WOMEN - Gulhayo Pulatova (Bright Mind Publishing, 2025)
This article analyzes the psychophysiological basis of anxiety in pregnant women, the causes of these conditions, ways to identify them and reduce their negative consequences on a scientific basis. The article also provides a comprehensive scientific explanation based on existing scientific research, psychological theories and practical observations.
Keywords: Pregnancy, stress, anxiety, autonomic nervous system, HRV, cortisol, epigenetics, neuropsychological approach, psychoprevention, cognitive-behavioral therapy.